2020
DOI: 10.1101/2020.08.28.272039
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

gEAR: gene Expression Analysis Resource portal for community-driven, multi-omic data exploration

Abstract: The gEAR portal (gene Expression Analysis Resource, umgear.org) is an open access community-driven tool for multi-omic and multi-species data visualization, analysis and sharing. The gEAR supports visualization of multiple RNA-seq data types (bulk, sorted, single cell/nucleus) and epigenomics data, from multiple species, time points and tissues in a single-page, user-friendly browsable format. An integrated scRNA-seq workbench provides access to raw data of scRNA-seq datasets for de novo analysis, as well as m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…Of course, the differences between technologies used in the different studies come with distinct limitations, such as the numbers of genes associated with individual cells that could affect clustering outcomes. Integration into the gEAR data depository ( Orvis et al, 2020 ) provides an instrument for directly comparing the datasets. We found that cell density is an important variable for activating GER cell growth, and that direct cell contact is essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, the differences between technologies used in the different studies come with distinct limitations, such as the numbers of genes associated with individual cells that could affect clustering outcomes. Integration into the gEAR data depository ( Orvis et al, 2020 ) provides an instrument for directly comparing the datasets. We found that cell density is an important variable for activating GER cell growth, and that direct cell contact is essential.…”
Section: Discussionmentioning
confidence: 99%
“…The RNA sequencing data generated in this paper is available from GEO with accession number GSE162308. The data are also available at gEAR, a gene Expression Analysis Resource ( Orvis et al, 2020 ), via PERMA-LINK https://umgear.org//index.html?layout_id=afd2eb77&gene_symbol_exact_match=1 . In gEAR, it is possible to project each gene’s expression value into the tSNE plot shown in Figure 3A , into a cochlear illustration with all cell types identified (based on Figures 2A – 2C ), as well as violin plots concordant with Table S3 .…”
Section: Methodsmentioning
confidence: 99%
“…In striking contrast, low PC1 maps to the pluripotent epiblast and emerging neural lineages (Figure 6E, in purple to pink and Figure S7B-D) with high expression of SOX3, LHX2, PAX6, EMX2, FEZF2, and RAX . The expression patterns of these and other genes can be explored at nemoanalytics.org/p?l=KimEtAL2021&g=FEZF2 , where we have used the gEAR and NeMO Analytics framework (Orvis et al, 2020) to construct an integrated gene expression data environment spanning the collection of in vivo and in vitro data examined in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The RNA sequencing data generated in this paper is stored in two SingleCellExperiment containers that are provided as Data S1 and S2. The data are also available at gEAR, a gene Expression Analysis Resource (https://umgear.org/) (Orvis et al, 2020)…”
Section: Star+methodsmentioning
confidence: 99%